Physical characterization and electrical conductivity of Li1.2Ti1.8Al0.2(PO4)3 and Li1.2Ta0.9Al1.1(PO4)3 NASICON material - Mohammed, Isah Kimpa; Mayzan, Mohd Zul Hilmi; Esa, Fahmiruddin; Yabagi, Jibrin Alhaji; Nmaya, Muhammad Muhammad; Agam, Mohd Arif (International Journal of Integrated Engineering, 2019)
Sodium superionic conducting materials (NASICON) are promising solid electrolytes for Li-ion batteries and suitable to be used in the area that requires high energy density as well as rechargeable power sources. Fabrication of all-solid-state Li battery with non-flammable ceramics electrolyte has been strongly required to solve safety issues of present Li batteries. In this study, lithium titanium aluminium phosphate Li1+xTi2-xAlx(PO4)3, LTAP (x = 0.2) and lithium tantalum aluminium phosphate Li1+2xTa1-xAlx+1(PO4)3, LTaAP (x = 0.1) were prepared via conventional solid state reaction techniques at various sintering temperature ranging from 700 to 1000 Â°C. LTAP and LTaAP compositions attain their optimum sintering temperature at 800 Â°C. Physical properties of LTAP and LTaAP show the bulk density of 2.83 and 3.63 g/cm3 which resulted into high densification of the material. The XRD analysis revealed NASICON crystalline phase dominated by LiTi2(PO4)3 and minor impurity phases for LTaAP composition. Bulk conductivity values for LTAP and LTaAP were found to be 1.06 x 10-4 and 9.854 x 10-6 S/cm at room temperature. LTAP had better conductivity behavior compare to LTaAP composition which could be due to differences in their ionic radius (titanium, 0.605 nm tantalum, 0.64 nm and the aluminium, 0.53 nm) in sizes, though the conductivity obtained for both compositions has the capacity to serve as solid electrolyte material could be used in lithium ion rechargeable battery.